ESTRUS INDUCTION AND FERTILITY RESPONSE IN POSTPARTUM ANESTRUS GIR COWS - RAMAKRISHNAN, AMMU; DHAMI, A J; NAIKOO, M; PARMAR, B C; DIVEKAR, B S (The Indian Journal of Animal Reproduction, 2023)
The study was aimed at induction/synchronization of estrus in suckler postpartum anoestrus/ suboestrus Gircows (n=18) of an organized farm . The anoestrus/suboestrus cows were divided into 3 equal groups each of 6animals, and a group of 6 normal cyclic cows was kept as control. Three standard synchronization protocolsinitiated around day 90 to 92 postpartum were CIDR, Ovsynch, and Cosynch, considering the day offirst GnRHinjection or CIDR insertion as day 0. The animals were bred by fixed-time Al (FTAI). Pregnancy was confirmed perrectum on day 45 post-Al. Plasma progesterone was estimated by RIA on day O (day offirst treatment), 7 (day ofPG injection), 9/10 (day of estrus/Al) and on day 10, 20, 30 and 40 post-Al. The estrus induction response asnoted by uterine tone and mucus discharge was 100% in all 3 groups, but the behavioural signs were observed in83.33, 83.33 and 100.00 % of cows under CIDR, Ovsynch and Co-synch protocols, respectively. The conceptionrates at induced estrus (FTAI) in CIDR, Ovsynch and Cosynch protocol were 50.00, 50.00 and 33.33 %, respectively.The corresponding overall conception rates of 2 cycles post-treatment were 83.33 (5/6), 66.66 (4/6), and 83.33 (5/6) %. In control group, the first service and overall conception rates were 33.33 and 66.66 (4/6) %, respectively.The results were the best with CIDR, followed by Cosynch and Ovsynch protocol. The plasma progesterone (ng/ml) concentrations were significantly (P
Keywords: Gir cows; Estrus synchronization; CIDR; Ovsynch and Cosynch; Plasma progesterone